Critical illness-associated cerebral microbleeds in COVID-19. Issue 5 (October 2020) - Vattoth, Surjith; Abdelhady, Mohamed; Alsoub, Hussam; Own, Ahmed; Elsotouhy, Ahmed
We are reporting the imaging findings of the rare entity of critical illness-associated cerebral microbleeds in a COVID-19-positive 66-year-old woman with hypoxic respiratory failure, who was eventually intubated and ventilated. Multiple scattered cerebral microhaemorrhages diffusely distributed in the juxtacortical white matter and internal capsule region, sparing the deep and periventricular white matter, basal ganglia, thalami and cortex were seen, which is a unique imaging finding in critically ill patients with respiratory failure and hypoxemia requiring mechanical ventilation. The mechanism underlying these microhaemorrhages relates to the endpoint of critical illness, rather than a specific underlying disease.